Image 2003 : (World scientific, 2003)
An image is better than one thousand words; so it was straightforward to apply visual language in the field of computer science. Nowadays everything that appears on a computer screen is an image, regardless of whether it is a word or a picture. Is it possible to realize an e-learning program without working in terms of images? The answer is undoubtedly no, even if several problems arise in this context: the qualitative and quantitative content of the image we need to use for a specific task; the psychological effect on the user, including the level of attention and the correct perception of the image significance. Most of these problems form the basis of image-understanding techniques.